High-thermal-conductivity PVC composite material as well as preparation method and application thereof
By using thermal fillers such as nanoboronitride, nanosilicon carbide or nanoalumina in PVC composite materials, combined with coupling agent and gelation accelerator, the problem of insufficient thermal conductivity in PVC floor heating sealed electric heater is solved, and high The improvement of thermal conductivity and insulation performance avoids the risks of fire and leakage.
Patent Information
- Application Number
- CN202411174885.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2024-12-27
AI Technical Summary
In the existing PVC floor heating sealed electric heater belt, the thermal conductivity of the composite material of the electric heating wire and PVC film is insufficient, resulting in untimely transfer of heat energy, which is prone to risks such as hole breakage, leakage and fire.
Using nanoboronitride, nanosilicon carbide or nanoalumina as thermal conductivity fillers, combined with coupling agent, gelation accelerator and relatively few plasticizers, improve the thermal conductivity and insulation performance of PVC composite materials and ensure the thermal conductivity and insulation properties with electric heating wires. a good compound.
It effectively improves the thermal conductivity of PVC composite materials, prevents fire risks, and maintains high tensile strength and elongation at break, ensuring good insulation performance and high temperature resistance.
Smart Images

Figure BDA0005010448200000061 
Figure BDA0005010448200000062 
Figure BDA0005010448200000071
Abstract
Description
Technical Field
[0001] The invention relates to the field of PVC products, in particular to a high thermal conductivity PVC composite material and a preparation method and application thereof. Background Art
[0002] Polyvinyl chloride resin (PVC) has a wide range of applications in the field of home decoration due to its excellent chemical corrosion resistance, mechanical properties, and insulation properties, such as cabinets, wall panels, quick-release panels, etc. At present, a new application is to seal PVC floor heating electric belts (electric floor heating films), or more specifically, to stick the heating wires between PVC films. In order to compound the heating wires with the PVC film through a hot pressing process, it is often necessary to introduce relatively more plasticizers into the PVC film. However, more plasticizers also reduce the thermal conductivity of the PVC film. Specifically, the general PVC film can reach 0.13~0.21W·m -1 ·K -1 When the plasticizer is high, it is only 0.14 to 0.17 W·m -1 ·K -1 This results in the heat generated by the heating wire not being transferred in time, which can easily cause holes, leakage, and even fire. Summary of the invention
[0003] Based on this, the purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a high thermal conductivity PVC composite material and a preparation method thereof, which can effectively improve the thermal conductivity and insulation performance, and can achieve good compounding with the heating wire, so that it can be used in electric floor heating films.
[0004] To achieve the above object, the technical solution adopted by the present invention is: a high thermal conductivity PVC composite material, comprising the following components in parts by weight:
[0005] 55-65 parts of polyvinyl chloride resin, 25-35 parts of plasticizer, 1-3 parts of heat stabilizer, 0.5-3 parts of gelling accelerator, 0.5-3 parts of coupling agent, 10-20 parts of thermal conductive filler, 0.1-10 parts of auxiliary agent;
[0006] Wherein, the thermal conductive filler is selected from one or more of nano boron nitride, nano silicon carbide, nano silicon nitride or nano aluminum oxide.
[0007] The present invention adopts one or more of nano boron nitride, nano silicon carbide, nano silicon nitride or nano alumina as thermal conductive fillers. First, it can effectively improve the thermal conductivity of PVC composite materials, improve thermal conductivity, prevent partial melting, and prevent risks such as fire. Second, through the mutual cooperation of coupling agent, gelling accelerator, and thermal conductive filler, the thermal conductive filler has good compatibility with the PVC system, will not significantly destroy the entanglement of molecular chains, and maintain the PVC composite material with high tensile strength and elongation at break. Third, under the condition of using a relatively small amount of plasticizer, the hardness of the PVC composite material will not be greatly increased, making it difficult to compound with the heating wire. Fourth, the PVC composite material has better insulation performance to prevent leakage.
[0008] The amount of polyvinyl chloride resin (PVC) is 55 to 65 parts, exemplarily 57, 59, 61 or 63 parts, but not limited thereto, preferably 60 to 65 parts.
[0009] Among them, the plasticizer can be a common phthalate plasticizer, a phosphate plasticizer or a polyester plasticizer in the art, exemplified by diisodecyl phthalate, diisooctyl phthalate, and tricresyl phosphate, but not limited thereto. The plasticizer can reduce the glass transition temperature and flow temperature of PVC, improve plasticity, and optimize the degree of composite with the heating wire in the later stage. The amount of plasticizer is 25 to 35 parts. If the amount is too large, the thermal conductivity of the PVC composite material will be greatly reduced. Exemplarily, the amount of plasticizer is 26 parts, 28 parts, 30 parts, 32 parts or 34 parts, but not limited thereto. Preferably, the amount of plasticizer is 28 to 34 parts.
[0010] Among them, the heat stabilizer is a barium zinc heat stabilizer or a calcium zinc heat stabilizer commonly used in the art, but is not limited to this. The heat stabilizer can improve the stability of PVC composite materials at higher temperatures and reduce discoloration and yellowing. It should be noted that in PVC floor heating sealed electric belts, the heating temperature of the heating wire often reaches 70°C to 80°C. Long-term high temperature can easily cause the PVC composite material to discolor and yellow, component segregation, and produce odors. The introduction of a heat stabilizer can effectively improve thermal stability and weaken adverse effects. Specifically, the amount of the heat stabilizer is 1 to 3 parts, exemplified by 1.3 parts, 1.5 parts, 1.7 parts, 1.9 parts, 2.1 parts, 2.3 parts, 2.5 parts, 2.7 parts or 2.9 parts, but not limited to this. Preferably, it is 1 to 2 parts.
[0011] Among them, the main function of the gelling accelerator is to improve the fluidity of the PVC material at high temperature, improve the gelling efficiency, and optimize the compatibility of the PVC system with the thermal conductive filler. Specifically, the gelling accelerator can be selected from ACR (core-shell structure acrylic resin) and oxidized polyethylene wax commonly used in the art, but not limited to this. The amount of the gelling accelerator is 0.5 to 3 parts, and illustratively 0.8 parts, 1.1 parts, 1.4 parts, 1.7 parts, 2 parts, 2.3 parts, 2.6 parts or 2.9 parts, but not limited to this. Preferably, it is 0.5 to 1 part.
[0012] The coupling agent can improve the compatibility of the thermal conductive filler with the PVC matrix and optimize the dispersion of the thermal conductive filler. Specifically, the amount of the coupling agent is 0.5 to 3 parts, exemplarily 0.8, 1.1, 1.4, 1.7, 2, 2.3, 2.6 or 2.9 parts, but not limited thereto. Preferably, it is 0.5 to 1 part.
[0013] The amount of thermally conductive filler used is 10 parts to 30 parts, and exemplary amounts are 12 parts, 15 parts, 18 parts, 21 parts, 24 parts, or 27 parts, but not limited thereto.
[0014] The auxiliary agent may be a common colorant, mildewproofing agent, flame retardant, antioxidant, etc. in the art, but is not limited thereto. The amount of the auxiliary agent is 0.1 to 10 parts, exemplarily 0.8, 1.5, 2.2, 3, 3.5, 4.3, 5.4, 7, 8 or 9 parts, but is not limited thereto.
[0015] Preferably, in one embodiment of the present invention, the thermal conductive filler is a mixture of nano boron nitride and nano silicon carbide, and the weight ratio of the two is (5-15): (5-15). Specifically, the inventor unexpectedly found that when nano boron nitride and nano silicon carbide are used as thermal conductive fillers together, an effective thermal conductive network can be formed between the two at a lower filling amount, greatly improving the thermal conductivity efficiency, while also optimizing the electrical insulation performance; in addition, the amount of thermal conductive filler can be reduced to 10 to 20 parts.
[0016] Preferably, in one embodiment of the present invention, the weight ratio of nano hexagonal boron nitride powder to nano silicon carbide powder is (5-8): (10-15). It should be noted that compared with nano silicon carbide powder, nano boron nitride powder has stronger thermal conductivity, higher volume resistivity and better insulation, but the cost of one is very high, and it is more prone to agglomeration and has poor dispersion performance. For this reason, the present invention uses a relatively small amount of nano boron nitride. And by using ACR (core-shell structured acrylic resin) with a weight average molecular weight of ≥5 million as a gelling promoter, the overall volume resistivity of the PVC material is effectively improved, ensuring that it has better insulation performance. In addition, using ACR as a gelling promoter can effectively optimize water resistance. It should be noted that since some PVC floor heating sealing electric belts need to be laid with surface decorative materials such as tiles after laying, cement is often used for fixing; at this time, the PVC composite material needs to have a certain hardness to prevent wear, and it also needs to have a certain water resistance to prevent water vapor from penetrating into the PVC floor heating sealing electric belt.
[0017] Preferably, in one embodiment of the present invention, the plasticizer is a mixture of diisodecyl phthalate and polyester plasticizer; first, by combining the above two plasticizers, the PVC composite material can ensure appropriate softness when the plasticizer content is low, which is convenient for later compounding with the heating wire. Second, the use of the above combination of plasticizers can ensure that the plasticizer is stable during long-term high-temperature use and does not decompose to produce irritating odorous gases. Third, the insulation performance of the PVC composite material can be optimized. Fourth, the polyester plasticizer can be prevented from agglomerating during the processing process, thereby optimizing the processing efficiency. Fifth, fewer hydrophilic groups are introduced to avoid weakening the water resistance of the PVC material.
[0018] Specifically, the weight ratio of diisodecyl phthalate to the polyester plasticizer is 6-10:15-25. The molecular weight of the polyester plasticizer is 2000-4000.
[0019] Preferably, in one embodiment of the present invention, the degree of polymerization of the polyvinyl chloride resin is 1250-1350, which can meet the demand of long-term high temperature resistance and is easy to process.
[0020] Preferably, in one embodiment of the present invention, the coupling agent is an aminosilane coupling agent, exemplified by γ-aminopropyltriethoxysilane, γ-aminopropylmethyldiethoxysilane or 3-aminopropyltrimethoxysilane, but not limited thereto. γ-aminopropyltriethoxysilane is preferred. The aminosilane coupling agent can introduce amino groups on the surface of the thermally conductive filler, greatly optimizing the dispersibility, and can also improve the overall water resistance of the PVC composite material.
[0021] Preferably, in one embodiment of the present invention, the heat stabilizer is barium zinc stabilizer powder.
[0022] Preferably, in one embodiment of the present invention,
[0023] The additives include the following components by weight: 2 to 5 parts of titanium dioxide and 0.2 to 1 part of masterbatch. Among them, titanium dioxide can improve the weather resistance, chemical resistance and wear resistance of PVC composite materials, and can also optimize water resistance.
[0024] Correspondingly, the present invention also discloses a method for preparing a high thermal conductivity PVC composite material, which is used to prepare the above-mentioned high thermal conductivity PVC composite material, and comprises:
[0025] (1) mixing the components to obtain a mixture;
[0026] (2) Preliminarily plasticizing the mixture using an internal mixer to obtain a primary plastic material;
[0027] (3) plasticizing the primary plasticized material with an open mill for secondary plasticization and then feeding it into a single screw extruder for further plasticization and filtering to obtain a re-plasticized material;
[0028] (4) calendaring the composite plastic material to obtain a high thermal conductivity PVC composite material.
[0029] Preferably, in one embodiment of the present invention, step (1) comprises:
[0030] In step (1), the coupling agent is firstly mixed with the thermal conductive filler and then mixed with other components; and / or
[0031] In step (2), the mixture is preliminarily plasticized at 160° C. to 180° C.; and / or
[0032] In step (3), the temperature of the secondary plasticization is 165°C to 180°C, and the temperature of the third plasticization is 170°C to 190°C.
[0033] Preferably, in one embodiment of the present invention, in step (4), the composite material is subjected to 5-roll calendering, wherein the temperatures of the 5-roll calender are 195°C to 200°C, 190°C to 195°C, 185°C to 188°C, 185°C to 195°C and 170°C to 178°C, respectively.
[0034] Correspondingly, the present invention also discloses the application of the above-mentioned PVC composite material in electric floor heating film.
[0035] The implementation of the present invention has the following beneficial effects:
[0036] In the high thermal conductivity PVC composite material of the present invention, one or more of nano boron nitride, nano silicon carbide, nano silicon nitride or nano aluminum oxide is used as a thermal conductive filler, which can effectively improve the thermal conductivity of the PVC composite material, improve the thermal conductivity, and prevent partial melting, fire and other risks. Furthermore, the present invention makes the thermal conductive filler have good compatibility with the PVC system through the mutual coordination of the coupling agent, the gelling accelerator, and the thermal conductive filler. Moreover, the PVC composite material of the present invention will not significantly increase the hardness of the PVC composite material under the condition of using a relatively small amount of plasticizer, making it difficult to compound with the heating wire. In addition, the high thermal conductivity PVC composite material of the present invention has good insulation properties through the synergy of various components. DETAILED DESCRIPTION
[0037] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0038] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.
[0039] The raw materials used in the embodiments and comparative examples are described below, but are not limited to these materials:
[0040] A1: PVC resin, degree of polymerization 1300; TG-1300, Tosoh Chemical, Japan;
[0041] A2: PVC resin, degree of polymerization 800; S60, Formosa Plastics;
[0042] B1: Plasticizer: DIDP, commercially available;
[0043] B2: polyester plasticizer, molecular weight 3000, W-2370, DIC Corporation;
[0044] C: Heat stabilizer: Barium zinc stabilizer powder, RUP-177, ADEKA Corporation
[0045] D1: Gelation accelerator: oxidized polyethylene wax, number average molecular weight 3000; 316A, Honeywell, USA
[0046] D2: Gelation accelerator: ARC, weight average molecular weight about 5.3 million, K435-P, Dow Chemical;
[0047] E: γ-aminopropyltriethoxysilane, commercially available;
[0048] F1: nano-alumina, commercially available;
[0049] F2: Nano-silicon carbide, Xuzhou Jie Innovation Materials Technology Co., Ltd.;
[0050] F3: Nano hexagonal boron nitride, DK-BN-001, Beijing Dekedaojin Technology Co., Ltd.;
[0051] G: titanium dioxide, commercially available;
[0052] H: masterbatch, commercially available.
[0053] Example 1 to Example 8 and Comparative Example 1 to Comparative Example 4
[0054] The components and weight proportions of the high thermal conductivity PVC composite materials of Examples 1 to 8 and Comparative Examples 1 to 4 are shown in Table 1 and Table 2, and the preparation method thereof is as follows:
[0055] (1) mixing the coupling agent and the thermally conductive filler uniformly, and then mixing with other components to obtain a mixture;
[0056] (2) Preliminarily plasticizing the mixture at 165° C. to 170° C. using an internal mixer to obtain a primary plastic material;
[0057] (3) The primary plasticized material is plasticized at 170° C. to 180° C. by an open mill and then fed into a single screw extruder, plasticized again at 170° C. to 180° C. and then filtered to obtain a re-plasticized material;
[0058] (4) The composite plastic material is calendered by a five-roll calender to obtain a high thermal conductivity PVC composite material. The temperatures of the rollers in the five-roll calender are 198° C., 192° C., 186° C., 188° C. and 172° C. respectively.
[0059] Table 1
[0060]
[0061] Table 2
[0062]
[0063] The high thermal conductivity PVC composite materials of Examples 1 to 8 and Comparative Examples 1 to 4 were tested, and the specific method is as follows:
[0064] (1) Thermal conductivity: The high thermal conductivity PVC composite material was made into a standard sample with a side length of 10 mm and a thickness of 2 mm and tested according to ASTME 1461-107;
[0065] (2) Volume resistivity: Tested in accordance with GB / T 1410-2006
[0066] (3) Shore A hardness: tested in accordance with GB / T 531.1-2008;
[0067] (4) Tensile strength and elongation at break: tested in accordance with GB / T 1040-2006;
[0068] (5) Melt index: tested according to GB / T 3682-2000, the test conditions are 190℃ and 2.16kg weight pressure;
[0069] The specific test results are shown in Table 3:
[0070] Table 3
[0071]
[0072] From the comparison of Examples 4 to 7, it can be seen that when a mixture of nano-boron nitride and nano-silicon carbide in a specific ratio is used as a thermally conductive filler, not only the thermal conductivity is greatly improved, but also a relatively high volume resistivity is maintained, that is, better thermal conductivity and insulation properties are simultaneously guaranteed. In addition, its Shore hardness is relatively low and the melt index is relatively high, indicating that its processing performance is good.
[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A high thermal conductivity PVC composite material, characterized in that: The composition comprises the following components in parts by weight: 55 to 65 parts of polyvinyl chloride resin, 25 to 35 parts of plasticizer, 1 to 3 parts of heat stabilizer, 0.5 to 3 parts of gelling accelerator, 0.5 to 3 parts of coupling agent, 10 to 30 parts of thermal conductive filler, and 0.1 to 10 parts of auxiliary agent; Wherein, the thermal conductive filler is selected from one or more of nano boron nitride, nano silicon carbide, nano silicon nitride or nano aluminum oxide.
2. The high thermal conductivity PVC composite material according to claim 1, characterized in that: The thermal conductive filler is a mixture of nano boron nitride and nano silicon carbide, and the weight ratio of the two is 5-15:5-15.
3. The high thermal conductivity PVC composite material according to claim 1, characterized in that: The thermal conductive filler is a mixture of nano boron nitride and nano silicon carbide, and the weight ratio of the two is 5-8:10-15; and / or The gelling accelerator is a core-shell acrylic resin with a weight average molecular weight of ≥5 million.
4. The high thermal conductivity PVC composite material according to any one of claims 1 to 3, characterized in that: The plasticizer is a mixture of diisodecyl phthalate and polyester plasticizer; The weight ratio of diisodecyl phthalate to polyester plasticizer is 6-10:15-25; The molecular weight of the polyester plasticizer is 2000-4000.
5. The high thermal conductivity PVC composite material according to any one of claims 1 to 3, characterized in that: The degree of polymerization of the polyvinyl chloride resin is 1250 to 1350; and / or The coupling agent is an aminosilane coupling agent; and / or The heat stabilizer is barium zinc stabilizer powder.
6. The high thermal conductivity PVC composite material according to any one of claims 1 to 3, characterized in that: The auxiliary agent comprises the following components by weight: 2 to 5 parts of titanium dioxide and 0.2 to 1 part of masterbatch.
7. A method for preparing a high thermal conductivity PVC composite material, used for preparing the high thermal conductivity PVC composite material as claimed in any one of claims 1 to 6, characterized in that: include: (1) mixing the components to obtain a mixture; (2) Preliminarily plasticizing the mixture using an internal mixer to obtain a primary plastic material; (3) plasticizing the primary plasticized material with an open mill for secondary plasticization and then feeding it into a single screw extruder for further plasticization and filtering to obtain a re-plasticized material; (4) calendaring the composite plastic material to obtain a high thermal conductivity PVC composite material.
8. The method for preparing a high thermal conductivity PVC composite material according to claim 7, characterized in that: In step (1), the coupling agent is firstly mixed with the thermal conductive filler and then mixed with other components; and / or In step (2), the mixture is preliminarily plasticized at 160° C. to 180° C.; and / or In step (3), the temperature of the secondary plasticization is 165°C to 180°C, and the temperature of the third plasticization is 170°C to 190°C.
9. The high thermal conductivity PVC composite material according to claim 7, characterized in that: In step (4), the composite plastic material is subjected to five-roll calendering, wherein the temperatures of the rollers in the five-roll calender are 195°C to 200°C, 190°C to 195°C, 185°C to 188°C, 185°C to 195°C and 170°C to 178°C, respectively.
10. Use of the high thermal conductivity PVC composite material as described in any one of claims 1 to 6 in electric floor heating films.
